Negotiating The Social Body: The Autonomy and Subjectivity of Javanese Female Singer “Sinden” in Eka Uget-Uget - Vici Duta Febriansyah; Sri Kusumo Habsari; Eva Farhah (International Journal of Science and Applied Science: Conference Series, 2022)
Sinden originated from the word "pasindhian" which means have many very treasury will song or singing (singing song). Sinden also called waranggana, "wara" means someone who is sex female and "anggana" means alone. Swarawati sued have ability broad communication, beautiful body and face, as well as ability sing songs Java. This post discuss subjectivity and autonomy body sinden through figure artist Eka's woman is passionate. how Sinden Eka Uget negotiate and seek subjectivity in art show puppet skin. Research results this show that subjectivity Eka Uget-Uget's body, how is it? still could show autonomy her body instead Becomes Eka Uget-Uget objek object rather Becomes Subject in the her body. He can make her body as subject. In Thing this, he alone Becomes the controlling actor her body alone. He could have position high bargaining and negotiation when he obey or entertain public. Paper this use method qualitative with collected data from Eka Uget-Uget's YouTube videos and several re-uploaded videos. through study this show that sinden entitled for appreciate and express her body alone without must intervened by other forces outside her body.